Search for the associated production of charm quarks and a Higgs boson decaying into a photon pair with the ATLAS detector - Aad, G. (2025)
A search for the production of a Higgs boson and one or more charm quarks, in whichthe Higgs boson decays into a photon pair, is presented. This search uses proton–protoncollision data with a centre-of-mass energy of 13 TeV and an integrated luminosityof 140 fb−1 recorded by the ATLAS detector at the Large Hadron Collider. The analysisrelies on the identification of charm-quark-containing jets, and adopts an approach based onGaussian process regression to model the non-resonant di-photon background. The observed(expected, assuming the Standard Model signal) upper limit at the 95% confidence level onthe cross-section for producing a Higgs boson and at least one charm-quark-containing jet thatpasses a fiducial selection is found to be 10.6 pb (8.8 pb). The observed (expected) measuredcross-section for this process is 5.3 ± 3.2 pb (2.9 ± 3.1 pb).